EFEKTIVITAS JALAN HUTAN DI SUATU PERUSAHAAN HUTAN DI RIAU - Dulsalam Dulsalam; Jurnalis Thaib (Jurnal Penelitian Hasil Hutan, 1990)
An  investigation on the effectiveness of forest  roads was conducted at PT  Siak  Raya  Timber in Riau in 1989.  The objective is to find  out  the  information on construction and  uses of forest roads. The length of main and  branch roads and target and actual productions   during the latest six years (from1983/1984  to 198811989)  were collected.  The investigation  results reveal that: 1.The  length  of  forest   roads  built  annually   by  PT  Siak  Raya  Timber  ranged from  16  km  (consisting  of  10 km  main and  6 km branch  roads)  to 85 km  (consisting  of 65 km  main and 20 km branch roads), with an average of 21.66 km (consisting of 11.68 km  main and 20 km branch roads). 2.The annual  felling area of PT Siak Raya Timber was 2,600 ha. The road densities  ranged from  6.16 m/ha  to 32.69  m/ha with  an  average of 21.66 m/ha. The road density is some what high compared  to that stated  in the Forest Agreement. 3.The actual production of  logs at PT Siak Raya Timber ranged from  21,225.65 m3/year  to 47,199.04 m3/year  with an average of 34,417.03 m3/year. 4.The  differencf  between target and actual production averages was relatively large i.e.  75,500 m3/year compared to 34,417.03 m3/year. The effectiveness of forest roads  ranged  from 268.67m3/km-year to 2,305.86 m3/km-year with  an average of 1,010 m3/km-year.